Modifying Plastic Balls in Seated Volley Ball Games for the Disabled - Barlaman, Revido Yogi; Yono, Topo; Apriliyanto , Rizki (Gladi : Jurnal Ilmu Keolahragaan, 2026)
Special education for the disabled requires facilities or learning media as a supporting tool in teaching and learning activities. The lack of volleyball media for the disabled makes learning less effective and efficient because volleyball is not efficient for students with disabilities. There needs to be a modification of the ball that is safe and comfortable for the disabled. This study aims to determine how to make a modification of a plastic ball as a supporting tool for volleyball learning media for the disabled. A modified plastic ball with a size 4, weighing 185 grams, a reflectivity of 83 cm from 120 cm is provided as a solution media for volleyball learning. The methods used are preparation, implementation, and evaluation. Learning using modified plastic ball media is very helpful in learning in terms of balancing a sense of security and pleasure with students, the ball is easy to play according to students of Harapan Pelangi Kalisat Special School, and as a supporting tool for volleyball learning for students with disabilities.